The effectiveness of using local exhaust ventilation, HEPA filter, and dental aerosol suction on indoor air quality - Alchusnah, Retno Hayati; Sarastuti, Dewi; Hidayati, Lia Fetti; Septiantari, Fatimah; Lasara, Belladina Yusi (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: The emergence of COVID-19 pandemic that occurred at the end of December 2019 in Wuhan, China, was a health crisis that greatly affected the world. Therefore, dentists and dental nurses are professionals who have a very high risk of being exposed to the droplets and aerosol particles generated during dental procedures. Furthermore, they also have a high risk of cross-infection from exposure to microorganisms in blood, saliva, droplets, and instruments contaminated with blood, saliva, and tissue debris. This study aims to analyze the effectiveness of using exhaust fan wall/Local Exhaust Ventilation (LEV), HEPA filter, and dental aerosol suction in the dental clinic of Academic Hospital Gadjah Mada University. Methods: The type of the research is analytical observational study. This study measured temperature, humidity, ACH and the microbial load in the 3 dental clinic rooms of Sadewa 1 RSA UGM in September 2020, using an analytical observational method with ANOVA to determine the effect of using a LEV, HEPA filter and dental aerosol suction in the dental clinic. Results: Dental clinic equipped with a LEV, HEPA filter, and dental aerosol suction, was negatively associated with room humidity levels, with a Pearson correlation of (-0.777), air humidity correlated with microbial load (0.242), but the correlation was not large. From the ANOVA results, the use of LEV, HEPA filter and dental aerosol suction against humidity has a significant effect on reducing the humidity in the dental clinic with p value 0.05. Conclusion: The use of an oral LEV, HEPA filter, and dental aerosol suction has an effect on reducing air humidity and decreasing the microbial load, affects the number of particles or droplets in dental clinics, and affects ACH.Keywords: local exhaust ventilation, HEPA filter and dental aerosol suction, microbial load, humidity